2017
DOI: 10.1111/hypa.12351
|View full text |Cite
|
Sign up to set email alerts
|

The Underrepresentation of Women in Prestigious Ethics Journals

Abstract: The main goal of this study is to determine whether women are underrepresented in prestigious ethics journals relative to their representation in the field of ethics. Our study proceeds in three steps. Step one: we estimate the percentage of women who specialize in ethics. Step two: we estimate the percentage of articles in prestigious ethics journals that are authored by women. Step three: we examine whether there is any difference between the percentage of women who specialize in ethics and the percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…For more on professional performance and participation of women in philosophy, see Irvin (2014) and Schwitzgebel (2015a;2015b;2015c). For more on the representation of women authors in philosophy journals, see West, Jacquet, King, Correll, & Bergstrom (2013), Krishnamurthy (2017), Krishnamurthy, Liao, Deveaux, & Dalecki (2017), Saul (2017), and Schwitzgebel & Jennings (2017).…”
Section: Methodsmentioning
confidence: 99%
“…For more on professional performance and participation of women in philosophy, see Irvin (2014) and Schwitzgebel (2015a;2015b;2015c). For more on the representation of women authors in philosophy journals, see West, Jacquet, King, Correll, & Bergstrom (2013), Krishnamurthy (2017), Krishnamurthy, Liao, Deveaux, & Dalecki (2017), Saul (2017), and Schwitzgebel & Jennings (2017).…”
Section: Methodsmentioning
confidence: 99%
“…And if women are not submitting as much, why is this the case? A recent paper by Krishnamurthy et al (2017) found that women are underrepresented in ethics journals, once we consider the number of women specialising in the given topic. That is, after accounting for the general underrepresentation of women in philosophy, women are still even further underrepresented in top ethics journals.…”
Section: Women In Philosophy Journalsmentioning
confidence: 99%
“…This has included volumes on women philosophers throughout history (Waithe 1987(Waithe , 1990(Waithe , 1994Atherton 1994;Warnock 1996; Buxton and Whiting 2020). But it has also included pressure from philosophers themselves that aim to change the representation, position, and treatment of women and other marginalised groups within the academy (Tyson 2018;Holroyd and Saul 2018;Beebee andSaul 2021, 2011;Krishnamurthy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These journal quotas—both for submission and for acceptance—appear to correspond with the current population of women in philosophy. Since, however, the Journal of Moral Philosophy is a journal that, like Ethics , addresses an area of philosophy in which women are comparatively well represented (see section 3), a submission rate of 23 percent appears in a less positive light (Krishnamurthy et al ; Haslanger , 215). Moreover, the idea that “women ‘just aren’t as interested’ in philosophy of mind, philosophy of language, and such, .…”
Section: On Submission and Acceptance Ratesmentioning
confidence: 99%